2020
DOI: 10.1002/cncr.33160
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors for mortality in hematologic patients affected by COVID‐19

Abstract: Background Patients with cancer are considered highly vulnerable to the recent coronavirus disease 2019 (COVID‐19) pandemic. However, there are still few data on COVID‐19 occurring in hematologic patients. Methods One hundred two patients with COVID‐19 symptoms and a nasopharyngeal swab positive for severe acute respiratory syndrome coronavirus 2 seen at 2 hematologic departments located in Lombardy, Italy, during March 2020 were studied. Risk factors for acquiring COVID‐19 were analyzed by comparisons of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
103
3
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 18 publications
(53 reference statements)
8
103
3
5
Order By: Relevance
“…Their subgroup analyses provide some possible clues with the highest risk for patients with lung cancer and haematological cancer, that is, patients with either severe pulmonary disease or immune dysfunction [5]. From previous studies, patients with haematological cancers and COVID-19 has had high CFRs -mostly 30% or higher [9,[13][14][15][16][17][18].…”
Section: Editorialmentioning
confidence: 99%
“…Their subgroup analyses provide some possible clues with the highest risk for patients with lung cancer and haematological cancer, that is, patients with either severe pulmonary disease or immune dysfunction [5]. From previous studies, patients with haematological cancers and COVID-19 has had high CFRs -mostly 30% or higher [9,[13][14][15][16][17][18].…”
Section: Editorialmentioning
confidence: 99%
“…In conclusion, we consider that the positive outcomes of TKI‐treated CML patients with COVID‐19, including a lower frequency of SARS‐CoV‐2 infection and a higher survival rate, strengthen the hypothesis that these drugs might be beneficial in the treatment of this disease. Hence, we believe that a more detailed description by Cattaneo et al 1 about deceased subjects with CML under TKI therapy in their study would be valuable. Finally, further clinical research should be encouraged to assess the effectiveness of imatinib and other related TKIs in COVID‐19.…”
mentioning
confidence: 99%
“…In an article previously published in Cancer , Cattaneo et al 1 analyzed a cohort of patients with coronavirus disease 2019 (COVID‐19) and hematological malignancies in March 2020, and they highlighted that subjects with chronic myeloid leukemia (CML) had a lower than expected frequency of COVID‐19. The authors linked this observation to the lower level of immunodeficiency seen in CML and to a potential protective role of tyrosine kinase inhibitors (TKIs) based on the possible antiviral activity of these drugs.…”
mentioning
confidence: 99%
“…We thank Morales‐Ortega and his colleagues for their interest in our study 1 and particularly in patients with chronic myeloid leukemia (CML).…”
mentioning
confidence: 99%
“…In our study, 1 we evaluated the incidence of coronavirus disease 2019 (COVID‐19) in March 2020 according to hematological diagnosis in the Brescia cohort, and we observed that COVID‐19 was contracted by none of the patients affected by CML in the Brescia cohort and by 2 patients in the Milan cohort. A low incidence of COVID‐19 in patients with CML has been described in other studies 2,3 .…”
mentioning
confidence: 99%